2012
DOI: 10.1186/2191-2858-2-9
|View full text |Cite
|
Sign up to set email alerts
|

Four butyrolactones and diverse bioactive secondary metabolites from terrestrial Aspergillus flavipes MM2: isolation and structure determination

Abstract: The chemical constituents and biological activities of the terrestrial Aspergillus flavipes MM2 isolated from Egyptian rice hulls are reported. Seven bioactive compounds were obtained, of which one sterol: ergosterol (1), four butyrolactones: butyrolactone I (2), aspulvinone H (3), butyrolactone-V (6) and 4,4'-diydroxypulvinone (7), along with 6-methylsalicylic acid (4) and the cyclopentenone analogue; terrien (5). Structures of the isolated compounds were deduced by intensive studies of their 1D & 2D NMR, MS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 34 publications
(40 reference statements)
0
31
0
Order By: Relevance
“…Inspection of the 1D-and 2D-NMR data revealed that it had similar structure to that of compound 4 except an additional methine group d(H) 3.38 (H-C(5″)), d(C) 72.5 (C(5″)). 1 Fig. 4) indicated that the methine group was located at C(5″).…”
Section: Identification and Structure Elucidationmentioning
confidence: 99%
See 1 more Smart Citation
“…Inspection of the 1D-and 2D-NMR data revealed that it had similar structure to that of compound 4 except an additional methine group d(H) 3.38 (H-C(5″)), d(C) 72.5 (C(5″)). 1 Fig. 4) indicated that the methine group was located at C(5″).…”
Section: Identification and Structure Elucidationmentioning
confidence: 99%
“…In recent decades, numerous bioactive natural products have been isolated from strains of bacteria collected from different environments such as plants, animals, soils and sediments. [1] Among these bacteria, members of the order Actinomycetales play the most important roles in the production of secondary metabolites. [2] This order produce about 75% original scaffolds of marketed antibiotics, among which the genus Streptomyces stands out as the best explored.…”
Section: Introductionmentioning
confidence: 99%
“…The fungi isolated in the current study could be either obligatory or facultative 'marine fungi', hence other than using the term marine fungi, referring to them as marine/sponge-derived fungi is more appropriate as we have not determined the origin. A. flavipes has been reported from both terrestrial and marine sources [20][21][22][23] . Therefore, whether A. flavipes isolated in this study is a facultative marine fungus, that has been accumulated through filter feeding or an obligatory marine fungus, which has originated in the internal tissues, is open to conjecture.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, numerous biologically active natural products have been isolated from microbes collected from different environments such as plants, animals, soils, and sediments [3]. Marine microbes have been proven to possess a unique metabolic mechanism and an adaptive mechanism due to their special living environment, which is quite different from a terrestrial environment specialized in high pressure, high salt, low temperature, and a lack of nutrition [4].…”
Section: Introductionmentioning
confidence: 99%